Strategi Transformasi Konflik Search for Common Ground pada Konflik di Republik Demokratik Kongo (Studi Kasus Rehabilitasi Remaja Pasca Perang di Republik Demokratik Kongo) - Amalia Hasanah Ismail (Department of International Relations, Brawijaya University, 2017)
This research aims to analyze peace building strategy of the Search for Common Ground in Postwar Juvenile’s Rehabilitation in Democratic Republic of Congo are through formal and non formal education, the platform for juvenile to have voice in society, and through action or dialogue so that they can become Agent of Change in their communities. The Implementation of the Search for Common Ground program has a supporting factor such as the condition of juvenile who have creative and innovative minds, can be mobilized and mutually influence each other, as well as a good relationship with the military in the Democratic Republic of Congo. The inhibiting factors are the postwar trauma experienced by the community, the lack of funding, and lack of work management in Search for Common Ground. Spesifically, this research found that SFCG implement strategy as a part to build culture of peace in KongoKey Words: Peacebuilding, Culture of Peace, Conflict Transformation, International Non Governmental Organization